Experimental Analysis and Discussion on the Damage Variable of Frozen Loess. (13th March 2017) - Cai, Cong; Ma, Wei; Zhao, Shuping; Mu, Yanhu
Abstract : The damage variable is very important to study damage evolution of material. Taking frozen loess as an example, a series of triaxial compression and triaxial loading-unloading tests are performed under five strain rates of 5.0 × 10 −6 –1.3 × 10 −2 /s at a temperature of −6°C. A damage criterion of frozen loess is defined and a damage factor D c is introduced to satisfy the requirements of the engineering application. The damage variable of frozen loess is investigated using the following four methods: the stiffness degradation method, the deformation increase method, the dissipated energy increase method, and the constitutive model deducing method during deformation process. In addition, the advantages and disadvantages of the four methods are discussed when they are used for frozen loess material. According to the discussion, the plastic strain may be the most appropriate variable to characterize the damage evolution of frozen loess during the deformation process based on the material properties and the nature of the material service.